Lentiviral vector integration profiles differ in rodent postmitotic tissues - Bartholomä, Cynthia C.; Arens, Anne; Balaggan, Kamaljit S.; Yáñez-Muñoz, Rafael J.; Montini, Eugenio; Howe, Steven J.; Paruzynski, Anna; Korn, Bernhard; Appelt, Jens-Uwe; MacNeil, Angus; Cesana, Daniela; Abel, Ulrich; et al. (Molecular therapy, 2011)
Lentiviral vectors with self-inactivating (SIN) long terminal repeats (LTRs) are promising for safe and sustained transgene expression in dividing as well as quiescent cells. As genome organization and transcription substantially differs between actively dividing and postmitotic cells in vivo, we hypothesized that genomic vector integration preferences might be distinct between these biological states. We performed integration site (IS) analyses on mouse dividing cells (fibroblasts and hematopoietic progenitor cells (HPCs)) transduced ex vivo and postmitotic cells (eye and brain) transduced in vivo. As expected, integration in dividing cells occurred preferably into gene coding regions. In contrast, postmitotic cells showed a close to random frequency of integration into genes and gene spare long interspersed nuclear elements (LINE). Our studies on the potential mechanisms responsible for the detected differences of lentiviral integration suggest that the lowered expression level of Psip1 reduce the integration frequency in vivo into gene coding regions in postmitotic cells. The motif TGGAA might represent one of the factors for preferred lentiviral integration into mouse and rat Satellite DNA. These observations are highly relevant for the correct assessment of preclinical biosafety studies, indicating that lentiviral vectors are well suited for safe and effective clinical gene transfer into postmitotic tissues.
First published online: 14 December 2016
Gesehen am 17.02.2022